2004
DOI: 10.1073/pnas.0401672101
|View full text |Cite
|
Sign up to set email alerts
|

Simulation, experiment, and evolution: Understanding nucleation in protein S6 folding

Abstract: In this study, we explore nucleation and the transition state ensemble of the ribosomal protein S6 using a Monte Carlo (MC) Go model in conjunction with restraints from experiment. The results are analyzed in the context of extensive experimental and evolutionary data. The roles of individual residues in the folding nucleus are identified, and the order of events in the S6 folding mechanism is explored in detail. Interpretation of our results agrees with, and extends the utility of, experiments that shift -val… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 41 publications
(73 reference statements)
5
72
0
Order By: Relevance
“…O ur current understanding of the protein-folding nucleus is based on a synthesis of results from simulation (1) and experimental mapping of site-specific contacts in the transitionstate ensemble by protein engineering (2,3). From these results it is apparent that the free-energy landscape controlling the folding process is highly evolved, with few traps and a characteristic bias toward native contacts (4,5).…”
Section: Circular Permutation ͉ -Values ͉ Transition Statementioning
confidence: 99%
“…O ur current understanding of the protein-folding nucleus is based on a synthesis of results from simulation (1) and experimental mapping of site-specific contacts in the transitionstate ensemble by protein engineering (2,3). From these results it is apparent that the free-energy landscape controlling the folding process is highly evolved, with few traps and a characteristic bias toward native contacts (4,5).…”
Section: Circular Permutation ͉ -Values ͉ Transition Statementioning
confidence: 99%
“…The results suggest that the envelop of residues that normally protects the hydrophobic interior of the SOD monomer is largely unfolded in the transition-state ensemble. Although the precise nature of this outer boundary of the transition-state structure is intrinsically difficult to pin down (37,38), it can be safely concluded that the side chains with low values consolidate mainly on the downhill side of the folding barrier. Vice versa, these side chains define the regions of the SOD structure that ruptures early in the unfolding process, i.e., what is missing at the top has been lost on the way up.…”
Section: The Aposod Monomer Folds Cooperatively According To a Two-statementioning
confidence: 99%
“…Just like the -value analysis in experiments with real-world proteins, the folding probability analysis method has been extensively used to investigate the TSE in computer simulations of protein folding. 13,[34][35][36][37] The P fold method has one caveat though: it is computationally costly. 38 Here we perform extensive Monte Carlo simulations of a simple lattice protein model to construct and compare two ensembles of conformations representative of the TSE.…”
Section: Introductionmentioning
confidence: 99%